Development of Augmented Reality Application for Made-to-Order Furniture Industry in Pampanga, Philippines - Yambao, Jaymark A.; Miranda, John Paul P.; Pelayo, Earl Lawrence B. (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – The focus of the study was to develop a mobile application utilizing marker-less augmented reality for specific made-to-order products to support furniture and fixtures businesses. Method – The study implemented mixed-methodology to properly identify the various stakeholders' considerations in developing the application. Interviews with key informants were conducted to ensure that the features were appropriate for the intended user needs, and selected ISO standards were used as evaluation criteria. Results – The results indicate that the mobile application with marker-less AR technology was found to be highly acceptable by three evaluators (i.e., customers, owners, and IT experts). Conclusion – The study also highlighted the use of AR-related technology in this case, where marker-less has the potential to improve customer purchasing experience even further. Recommendations – Future studies may include using newer technologies to further improve the application. Practical Implications – The study suggests that Augmented Reality technology could be used to connect specific businesses directly to consumers regardless of setting or context.